1989
DOI: 10.1177/0013164489492021
|View full text |Cite
|
Sign up to set email alerts
|

Providing Item Feedback in Computer-Based Tests: Effects of Initial Success and Failure

Abstract: This study investigated the effects of providing item feedback on student achievement test performance and anxiety, and how these effects may be moderated by the amount of success and students experience on the initial items of the test. Introductory statistics students were randomly assigned to six forms of a computer-based algebra test that differed in terms of (a) the difficulty of the first five items, and (b) the type of item feedback provided. Although test performance was not affected significantly by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This behavior might allow appropriate use of time so that easier questions are answered quickly to devote more time for difficult questions. Indeed, it has been reported that examination-related anxiety is significantly reduced where students have the opportunity to skip and later return to more difficult questions (Wise et al, 1989). Such an advantage is not possible in the steeplechase format.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior might allow appropriate use of time so that easier questions are answered quickly to devote more time for difficult questions. Indeed, it has been reported that examination-related anxiety is significantly reduced where students have the opportunity to skip and later return to more difficult questions (Wise et al, 1989). Such an advantage is not possible in the steeplechase format.…”
Section: Discussionmentioning
confidence: 99%
“…3 In contrast, other studies have indicated that immediate feedback is associated with decreases in test anxiety. [19][20][21] In terms of student ability, performance for low-ability students may not be negatively impacted by immediate feedback examinations, whereas feedback may impair performance of high-ability students, 22 this would be difficult to assess in this cohort of students as most would be considered high-ability students based on course performance and their entrance criteria (eg, PCAT and grade point average).…”
Section: Discussionmentioning
confidence: 99%
“…For computer anxiety, previous research has not established whether this variable significantly affects computer test performance. One position in this debate suggests that computer anxiety can significantly affect test performance [16][17][18], while other research examining computer anxiety fails to find this relationship [8,19]. The Vispoel, Rocklin, and Wang study also found similar results for another individual variable, verbal self-concept, which was based on the participants' belief in their ability to perform well on the administered vocabulary test [8].…”
Section: Introductionmentioning
confidence: 88%